The Concept of Karma Yoga and Its Relationship with Spiritual Intelligence and Employee Performance of LPD in Buleleng Regency - Adnyana, I Putu Agus; Kusuma, Gusti Putu Eka (Journal of Business on Hospitality and Tourism, 2020)
This study aimed to determine the concept of Karma Yoga in relationship with spiritual intelligence and employee performance of LPD in Buleleng Regency. The concept of Karma Yoga is a value of local genius that will provide guidelines for LPD employees in the form of sincerity in working as a basis for improving employee performance of LPD. The population in this study was all active LPDs in Buleleng Regency. Sampling in this study using random sampling technique. The data analysis technique used in this study was the Component based SEM, Partial Least Square (PLS) analysis method. The results showed that the concept of Karma Yoga and spiritual intelligence had a relationship with employee performance.